Implementasi Sistem Informasi Data Alumni Berbasis Web Pada SMP N 18 Bengkulu Selatan - Empi Desni Linia Junita; Khairil Khairil; Ricky Zulfiandry (UNIVED Press, 2025)
The development of information technology aims to facilitate various activities, including data management and the rapid and accurate presentation of information. SMP Negeri 18 South Bengkulu, the manual management of alumni data is considered inefficient and prone to data loss, necessitating a web-based information system capable of securely storing and presenting alumni data in a structured and easily accessible manner. This study aims to develop an alumni information system that can improve data management efficiency, accelerate information access, and reduce the risk of data loss or damage. The method used in developing this system is the waterfall approach, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The results of the study show that the developed information system functions well as an alumni information center, facilitates interaction between alumni and the school, and supports the school's professional image through integrated data management. Thus, this system makes a real contribution to improving the quality of alumni information services in the school environment